Key workers in Malaysia during the pandemic - Lin Lean Lim (International Labour Organization (ILO), 2022)
During the COVID-19 pandemic, the Malaysian government prioritized health and economic stimulus packages for the sectors considered "key" for the economy and gave little recognition to the workers making contributions to the functioning of daily lives. The paper documents the impacts on key workers in healthcare, food and beverages, transportation and delivery, security and cleaning services. For these key workers, the nature of their jobs, labour force status and personal characteristics exposed them to greater job stressors and demands and exacerbated their vulnerabilities. While the fluidity of the coronavirus situation and the dynamic socio-political context of the country imply that change is on-going, the suggestions for recognizing, valuing, protecting and empowering key workers are necessary for helping the country to build back better.
Keywords: 330; COVID-19